Phản ứng Kumada: những phát triển gần đây và ứng dụng trong tổng hợp hữu cơ - Thuận, Ngô Thị; Tuấn, Đặng Thanh (Vietnam Journal of Chemistry, 2015)
Kumada reaction (or Kumada-Tamao-Corriu reaction) is one of the most important C-C cross-coupling reactions. Recent developments of palladium (and nickel) catalyst systems allowed Kumada reaction to be carried out under mild conditions with the tolerance of functional groups. Organomagnesium reagents, the highly reactive nucleophiles for carbon–carbon bond forming reactions, were employed in many cross-coupling reactions, but have only recently been reported for highly efficient and (stereo)selective coupling reactions. This review highlighted the recent developments of Pd-(and Ni)-based catalyst systems with bulky phosphine, phosphonate or carbene ligands and new metal–halogen exchange procedures for the preparation of functionalized Grignard reagents. In addition, some practical applications of Kumada reaction in the total synthesis of bioactive natural products, pharmaceuticals and organic materials were reported.